Peran manajemen risiko dalam meningkatkan kinerja pengurus di Unit Kegiatan Mahasiswa Seni Religius - Kusuma, M.Alfarizi (Maliki Interdisciplinary Journal, 2024)
The purpose of this research is to determine how risk management plays a role in improving management performance in the Religious Arts Student Organization (UKM Seni Religius) at UIN Maulana Malik Ibrahim Malang. This study employs a qualitative descriptive approach using primary data and utilizes data collection techniques such as observation, interviews, and documentation. The research findings indicate that the Religious Arts Student Organization has implemented risk management steps. They have established an independent Council of Deliberation responsible for overseeing and reviewing organizational processes. Additionally, they conduct regular coordination meetings, which serve the purpose of managing risks to enhance management performance and achieve the organization’s goals.